Uncommon Pathways of Immune Escape Attenuate HIV-1 Integrase Replication Capacity - Brockman, Mark A.; Chopera, Denis R.; Olvera, Alex; Brumme, Chanson J.; Sela, Jennifer; Markle, Tristan J.; Martin, Eric; Carlson, Jonathan M.; Le, Anh Q.; McGovern, Rachel; Cheung, Peter K.; Kelleher, Anthony D.; et al. (Journal of Virology, 2012)
Attenuation of HIV-1 replication capacity (RC) has been observed for immune-mediated escape mutations in Gag restricted by protective HLA alleles. However, the extent to which escape mutations affect other viral proteins during natural infection is not well understood. We generated recombinant viruses encoding plasma HIV-1 RNA integrase sequences from antiretroviral-naïve individuals in early (N=88) and chronic (N=304) infection, and measured the in vitro RC of each. In contrast to previous studies for Gag, we observed little evidence that host HLA allele expression was associated with integrase RC. A modest negative correlation was observed between the number of HLA-B associated integrase polymorphisms and RC in chronic infection (R= −0.2 p=0.003); however, this effect was not driven by mutations restricted by protective HLA alleles. Notably, integrase variants S119R, G163E, and I220L, which represent uncommon polymorphisms associated with HLA-C*05, A*33, and B*52, respectively, correlated with lower RC (all q